Freestanding Artificial Synapses Based on Laterally Proton‐Coupled Transistors on Chitosan Membranes. (25th August 2015) - Liu, Yang Hui; Zhu, Li Qiang; Feng, Ping; Shi, Yi; Wan, Qing
<x xml:space="preserve">Abstract</x> Freestanding synaptic transistors are fabricated on solution‐processed chitosan membranes. A short‐term memory to long‐term memory transition is observed due to proton‐related electrochemical doping under repeated pulse stimulus. Moreover, freestanding artificial synaptic devices with multiple presynaptic inputs are investigated, and spiking logic operation and logic modulation are realized.